Pemasaran Gerilya (Guerilla Marketing) Sebagai Alternatif Pemasaran Konvensional - Situmorang, James Rianto (Jurnal Administrasi Bisnis, 2016)
Conventional marketing carried out by companies often require huge costs. Companies advertise their products on television, spread flyers and billboards in many places, conduct sales promotion like crazy, and so forth. Smaller companies generally have a modest marketing budget so it is difficult to compete with the marketing done by large companies. Some small companies try to find an alternative to using non-conventional ways of marketing, known as guerrilla marketing. One characteristic of guerrilla marketing is a low cost but has elements, creative, sensation, unique, humor, and surprises. Nowadays, guerrilla marketing is also done by major companies such as McDonalds, Nike, FedEx and many others.Â Â